Relación del índice tobillo-brazo y el riesgo cardiovascular según score de Framingham en pacientes hospitalizados en el servicio de medicina del Hospital Apoyo Iquitos "César Garayar García", 2022 - Alván Ríos, Sonia del Pilar (2023)
Cardiovascular diseases are by far the leading cause of death in the world. Several scales are available to predict cardiovascular events; however, difficulties continue to exist in its estimation in primary care. In this sense, the ankle-brachial index is a valid, reliable and easy to perform test. Therefore, the purpose of this work is to determine the relationship between the ankle-brachial index and cardiovascular risk according to the Framingham score in patients hospitalized in the Medical service of the Hospital Apoyo Iquitos “César Garayar García”, 2022. For this, an observational, analytical, cross-sectional and prospective study was as shown by 73 patients. Concluding that there is a statistically significant association between a very high cardiovascular risk and an ankle-brachial index less than 0.9 (OR: 6.2; 95% CI: 1.1 - 34.7).